PENERAPAN PENDIDIKAN HUKUM PADA SISWA SMA DALAM MEWUJUDKAN KESADARAN HUKUM DAN PENEGAKAN HUKUM DI SMA MUHAMMADIYAH 2 SEMARANG - Dyah Listyorini; Arikha Saputra; Fitika Andraini (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Indonesia is a state of law, therefore the law in Indonesia must be obeyed and enforced. To be able to obey and enforce the law, people must understand and understand what the law is. there are so many cases of law violations committed by high school students because they do not understand the law. This research is entitled